Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Kepercayaan Terhadap Kepuasan Konsumen Jasa Travel Umrah Dan Haji Pada Pt. Sebariz Warna Berkah Di Surabaya - Setyowati, Endang; Chulaifi, Muhammadl In’amu (JHP17 (Jurnal Hasil Penelitian), 2018)
This research aims to find out: the influence of quality of service (X 1) towards consumer satisfaction (Y) services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya, influence the perception Rates (X 2) towards consumer satisfaction (Y) and umrah travel services Haji at PT. Sebariz Color Blessing in Surabaya and the influence of trust (X 3) against the consumer satisfaction (Y) services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya and the influence of the quality of service, price, and the Perception of trust in partial towards customer satisfaction services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya. This research uses a quantitative approach by using the tool calculate the SPSS version 24.0 by taking samples of as many as 60 respondents from the consumer services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya. Data retrieval is obtained by using purposive sampling technique when the dissemination of questionnaires do. The results of this research were obtained through calculation using SPSS t test that on a free variable service quality (X 1) the magnitude of the value of significance is 0.004 0.005 <, this indicates that H0 is rejected and the H1 is accepted, so that the free variables quality of service (X 1) effect significantly partially towards customer satisfaction services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya. The second free variables i.e. perception of price (X 2) the magnitude of the value of significance is 0.100 > 0.005, this indicates that H0 is accepted and rejected, so H1 non variable perception of price (X 2) has no effect against a partially significant satisfaction consumer services travel Hajj and umrah at PT. Sebariz Color Blessing in Surabaya. And variable trust (X 3) the magnitude of the value of significance is 0.729 > 0.005, this indicates that H0 is accepted and rejected, so H1 non variable perception of price (X 2) has no effect against a partially significant consumer satisfaction services travel Hajj and Umrah at PT. Sebariz Color Blessing in Surabaya. Based on the analysis of the correlation coefficient (R) of 0.575. These values indicate that the relationship of quality of service (X 1), perceptions of price (X 2), and trust (X 3) and consumer satisfaction variable (Y) is strong. As for the coefficient of determination (R2) that shows the value of 0.331 which means that amounted to 33.1% consumer satisfaction can be explained by the variable quality of service (X 1), perceptions of price (X 2) and trust (X 3). While remaining 100% 33.1% = 66.9% influenced by variables other than the model that is examined. Keywords: quality of service, Price Perception, confidence, consumer satisfaction.